Associations of systemic immune-inflammation index and systemic inflammation response index with maternal gestational diabetes mellitus: Evidence from a prospective birth cohort study - Shuanghua Xie; Enjie Zhang; Shen Gao; Shaofei Su; Jianhui Liu; Yue Zhang; Yingyi Luan; Kaikun Huang; Minhui Hu; Xueran Wang; Hao Xing; Ruixia Liu; et al. (Chinese Medical Journal)
Abstract. Background:. The role of inflammation in the development of gestational diabetes mellitus (GDM) has recently become a focus of research. The systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI), novel indices, reflect the body’s chronic immune-inflammatory state. This study aimed to investigate the associations between the SII or SIRI and GDM. Methods:. A prospective birth cohort study was conducted at Beijing Obstetrics and Gynecology Hospital from February 2018 to December 2020, recruiting participants in their first trimester of pregnancy. Baseline SII and SIRI values were derived from routine clinical blood results, calculated as follows: SII = neutrophil (Neut) count × platelet (PLT) count/lymphocyte (Lymph) count, SIRI = Neut count × monocyte (Mono) count/Lymph count, with participants being grouped by quartiles of their SII or SIRI values. Participants were followed up for GDM with a 75-g, 2-h oral glucose tolerance test (OGTT) at 24–28 weeks of gestation using the glucose thresholds of the International Association of Diabetes and Pregnancy Study Groups (IADPSG). Logistic regression was used to analyze the odds ratios (ORs) (95% confidence intervals [CIs]) for the the associations between SII, SIRI, and the risk of GDM. Results:. Among the 28,124 women included in the study, the average age was 31.8 ± 3.8 years, and 15.76% (4432/28,124) developed GDM. Higher SII and SIRI quartiles were correlated with increased GDM rates, with rates ranging from 12.26% (862/7031) in the lowest quartile to 20.10% (1413/7031) in the highest quartile for the SII (Ptrend <0.001) and 11.92–19.31% for the SIRI (Ptrend <0.001). The ORs (95% CIs) of the second, third, and fourth SII quartiles were 1.09 (0.98–1.21), 1.21 (1.09–1.34), and 1.39 (1.26–1.54), respectively. The SIRI findings paralleled the SII outcomes. For the second through fourth quartiles, the ORs (95% CIs) were 1.24 (1.12–1.38), 1.41 (1.27–1.57), and 1.64 (1.48–1.82), respectively. These associations were maintained in subgroup and sensitivity analyses. Conclusion:. The SII and SIRI are potential independent risk factors contributing to the onset of GDM.